Trichoderma harzianum T-22 Induces Systemic Resistance in Tomato Infected by Cucumber mosaic virus - Vitti, Antonella; Pellegrini, Elisa; Nali, Cristina; Lovelli, Stella; Sofo, Adriano; Valerio, Maria; Scopa, Antonio; Nuzzaci, Maria (Frontiers in Plant Science, 2016)
Understanding the induction of plant defenses against viruses using biocontrol agents is essential for developing new strategies against these pathogens, given the ineffectiveness of chemical treatments. The ability of Trichoderma harzianum, strain T-22 (T22) to control Cucumber mosaic virus (CMV) in Solanum lycopersicum var. cerasiforme plants and the changes in the physiology of tomato treated/infected with T22/CMV were examined. Plant growth-promoting effects, photosynthetic performance, reactive oxygen species (ROS) scavenging enzymes, and phytohormones were investigated. T22 improved tomato growth in terms of plant height and improved photosynthesis, total chlorophyll content and plant gas exchange. In contrast, CMV induced a negative effect on dry matter accumulation and inhibited the photosynthetic capacity. The analysis of plant hormones demonstrated that treating with T22 before or simultaneously to CMV infection, led to a systemic resistance by jasmonic acid/ethylene and salicylic acid signaling pathways. Conversely, systemic resistance was abscissic acid-dependent when T22 treatment was administered after the CMV infection. In conclusion, the data reported here indicate that the T22-based strategy may be the most effective measure against CMV.